Relación Entre Biomasa Aérea Y Producción Primaria Neta Con Las Variaciones Estacionales De Precipitaciones Y Temperaturas En Pastizales Del Sur De La Provincia De Córdoba - Mónaco, Cerutti, A., N.; V. Santa., M. J. Rosa y (European Scientific Journal, ESJ, 2017)
Natural grasslands of the planet are very important reservoirs of flora and fauna that provide various ecosystem services benefits. To maintain and improve their condition, it is necessary to study them and understand their composition and functioning as well as their evolution over time. In the present work the influence of climatic variables, temperature and rainfall on the aerial biomass behavior and the net primary productivity of a pasture were analyzed. For this purpose, a natural pasture was located on the banks of the Chocancharava River, in the town of Río Cuarto. Monthly sampling (September 2014 - August 2015) was carried out, cutting aerial biomass at ground level with tusar scissors and collecting biomass and mulch in 10 quadrants of 0.5 x 0.5 m (0.25 m2) and dried in stove to constant weight. This material was separated into compartments: green (BV), dry (BS) and mulch (BM) to determined the available biomass. For statistical analysis, a completely randomized design (DCA) of fixed effects with Infostat program was used. The highest contribution of BV was in summer months, 4262 kg / ha of 8772 kg / ha corresponding to the total cycle. The highest BS was determined in winter with 2715 kg / ha of the total 6663 kg / ha. The litter presented a behavior similar to the BV, with the highest peaks in summer months 2478 kg / ha of 6004 kg / ha. The PPN presented a marked spring increase. Adding the positive increases in monthly PPN, a value of 1206.6 kg / ha * year was determined. Considering that higher temperatures and rainfall are recorded in summer (average 22 ° C and 422 mm), it could be assert that these variables would explain a significant part of the variability in the total aerial biomass production of the pasture.